Recurrent Dialysis Access Steal Syndrome in a Non-Mature AVF: A Case of Radial Artery Ligation Following Initial Venoplasty - Tangel, Stephanus; Sumangkut, Richard; Firmansah, Sigit (Medical Scope Journal, 2026)
Abstract: Dialysis access steal syndrome (DASS) is a rare but serious complication of arteriovenous fistula (AVF) used for hemodialysis (HD). While initial interventions such as venoplasty and banding are effective in many cases, recurrent steal syndrome can occur, which may necessitate a surgical intervention such as ligation. We reported a 63-year-old male presented with continuous pain in the left forearm at the AV shunt site for two days. The patient was referred to Kandou Hospital for further management due to suspected stenosis and risk of total occlusion. Vascular ultrasound and venography confirmed the diagnosis, followed by venoplasty, banding repair and central dialysis line insertion. Post-procedure angiography demonstrated restored, though weak, distal blood flow, but after three weeks, the patient returned with an edematous left distal limb and oxygen level of 93-96%.  The gold standard for DASS, ligation, was then performed. Although this patient experienced edema after the first procedure, the outcome after the second intervention was very good, and the patient did not report any recurrence. In conclusion, recurrent DASS, especially in a non-mature AVF, presents unique challenges in management. This case highlights the importance of continuous post-intervention monitoring, patient education on proper AVF care, and the need for escalation to more definitive treatments like radial artery ligation when initial interventions, such as venoplasty failed. After the second intervention, the outcome was very good, and the patient did not report any recurrence. Early recognition of complications, including patient-induced factors like AVF manipulation, is crucial to prevent further morbidity and ensure the preservation of vascular access. Keywords: steal syndrome; chronic kidney disease; hemodialysis; arteriovenous fistula; venoplasty; radial artery ligation